Bacteriological Study of Otitis Media and Its Antibiotic Susceptibility Pattern - Basnet, Rabina; Sharma, Sudarshan; Rana, Jid Chani; Shah, Pradeep Kumar (Journal of Nepal Health Research Council, 2017)
Background: Otitis Media is a prevailing and notorious infection in developing countries causing serious local damage and threating complication. Mainly in developing countries like Nepal, Otitis Media results because of illiteracy, poverty and poor hygiene. The aim of this study was to determine the profile of Otitis Media, its causative agents and their antibiotic susceptibility pattern.Methods: The study included 263 pus samples from 240 patients attending ENT department of Bharatpur hospital from May 2015 to January 2016. Samples were processed in microbiology department for bacteria using standard operating protocol. Antibiotic susceptibility testing was performed for all bacterial isolates by Kirby Bauer disc diffusion method and the results were interpreted according to clinical and laboratory standard institute (CLSI) guideline.Results: Out of 240 patients, 121 were female and 119 were male. Highest incidence of Otitis Media was observed in 1-10 year age group. Out of 263 samples taken from 240 patients, 216 showed bacterial growth. Gram negative bacteria predominated and the most common bacteria isolated were Staphylococcus aureus 36.11% followed by Pseudomonas aeruginosa 33.33% and Coagulase Negative Staphylococci 8.08%. All bacterial isolates were sensitive to gentamycin. Staphylococcus aureus was sensitive to Amikacin and gentamycin. All gram negative bacterial isolates were sensitive to Imipenem and gentamycin. 100% of Pseudomonas aeruginosa was sensitive to Imipenem.Conclusions: Staphylococcus aureus was the most predominant organism isolated from the pus swab followed by Pseudomonas aeruginosa and all the isolated organisms were sensitive to Gentamycin.